Analisa Faktor-faktor yang mempengaruhi Purchase Decision dengan Trust sebagai Variabel Mediasi - Lily Purwianti; Suryani Suryani (Universitas Internasional Batam, 2021)
Fast food is a restaurant that is liked by all people. The purpose of this study is to analyze the effect of media marketing on purchase decisions with trust as a mediating variable. The results of the study indicate that there is a significant positive relationship between Perceived Value to Purchase Decision, Perceived Value to Trust, Sales Promotion to Purchase Decision, Sales Promotion to Trust, Social Media Marketing to Purchase Decision, Social Media Marketing to Trust, Store Environment to Purchase Decision , Store Environment against Trust.